Analisis Kesuksesan Sistem Seleksi Mahasiswa Berprestasi dengan DeLone McLean Success Model - Alfaprasetyan, Kefas; Tambotoh, Johan Jimmy Carter (Jurnal Teknik Informatika dan Sistem Informasi, 2025)
Education is a very important thing where education can improve the quality and competitiveness of a person. Wonogiri Regency is one of the regions in Central Java that is currently struggling to improve the quality of human resources by increasing the interest in education of its people to the Higher Education level so that the Outstanding Student Scholarship program was launched. This study will analyze the success of the SIMAPRES website used for registration and selection of the scholarship program. The sample of this research is the applicants of the scholarship program who use the SIMAPRES website. The research model used is the DeLone & McLean IS Succes Model 2003 with 6 hypotheses and data processing using Partial Least Square-SEM which will show the correlation between variables from the model. This study tested a sample of 423 students applying for scholarship programs from various universities in Indonesia. From this sample, it was found that the six hypotheses showed a significant influence between variables with a T-Statistic value above 1.96, which also means that system quality, information quality, service quality have a good impact on the use and user satisfaction variables. From the results of the study it can be concluded that the SIMAPRES website has been quite successful in its use for registration and selection of the scholarship program.